2008
DOI: 10.1623/hysj.53.5.948
|View full text |Cite
|
Sign up to set email alerts
|

History of model development at Temple, Texas

Abstract: Model development at Temple, Texas, USA has a long history. Prior to the actual model development research, a hydrological data collection programme was established at Riesel, Texas (about 60 km northeast of Temple) in 1937. Data collected from the Riesel watersheds during 1937-2006 have been valuable in developing and testing models at Temple, as well as at other locations. Actual modelling research began in the mid-1960s with the development of single event models that served as building blocks for the compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(117 citation statements)
references
References 42 publications
(38 reference statements)
1
109
0
Order By: Relevance
“…It was developed to evaluate the effects of alternative management decisions on water resources and diffuse pollution in mesoscale and large river basins. A detailed history of SWAT's development can be found in Gassmann et al (2007) and Williams et al (2008). Here, it is only outlined briefly.…”
Section: A Glance At the Development History Of Swatmentioning
confidence: 99%
See 2 more Smart Citations
“…It was developed to evaluate the effects of alternative management decisions on water resources and diffuse pollution in mesoscale and large river basins. A detailed history of SWAT's development can be found in Gassmann et al (2007) and Williams et al (2008). Here, it is only outlined briefly.…”
Section: A Glance At the Development History Of Swatmentioning
confidence: 99%
“…The first paper, written by experts involved in the model development (Williams et al, 2008), presents an overview of the history of SWAT development. The first author has been working in this area since the mid-1960s, but the history started even earlier, in the mid-1930s, when it was decided that the US Soil Conservation Service evaluate experimentally the hydrological response from watersheds influenced by various management practices.…”
Section: This Special Issue On Advances In Ecohydrological Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of SWAT is a continuation of United States Department of Agriculture-Agricultural Research Service (USDA-ARS) modeling experience that spans a period of over 30 years [17,18]. Accurate calibration of hydrologic models (including SWAT) is very important in assessing the water budget of a watershed for sustainable water resources management [19].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with climate scenarios from general circulation models (GCMs), hydrological models are effective simulation tools to evaluate climate change effects on water resources at different spatial scales (Ficklin et al 2009, Moradkhani et al 2010, though uncertainty may exist in simulation results (Arnell 2011. The Soil and Water Assessment Tool (SWAT) is one of the most popular watershed modelling tools (Gassman et al 2007, Williams et al 2008. Numerous researchers have confirmed that SWAT is suitable for simulating climate change processes.…”
Section: Introductionmentioning
confidence: 99%